Method of Elimination Data Sources Conflicts in Information System - Levykin, V.; Evlanov, M. (My University, 2008)
Use of modern object-oriented methods of designing of information systems (IS) both descriptions of interrelations IS and automated with its help business-processes of the enterprises leads to necessity of construction uniform complete IS on the basis of set of local model of such systems. As a result of use of such approach there are the contradictions caused by inconsistency of the point of view of separate users IS. Besides similar contradictions arise while in service IS at the enterprise. It is necessary to note also, that now overhelming majority IS is developed and maintained as set of separate functional modules in uniform system can lead to a lot of problems. Among this problems it is possible to specify, for example, presence in modules of functions which are not used by the enterprise to destination, to complexity of information and program integration of modules of various manufactures, etc. In most cases there contradictions and the reasons, their caused, are consequence of primary representation IS as equilibrium steady system.
Keywords: Information system; dynamic system; information gene; metamodel; data sources conflict; synergetic; conflict elimination